Legal and Criminological Analysis of Cryptocurrency Money Laundering in Supreme Court Cassation Decision - Aria Perkasa Utama; Setiawan Noerdajasakti; Fachrizal Afandi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
The development of financial technology through blockchain-based crypto assets has given rise to new patterns of economic crime, particularly money laundering offenses. The decentralized, anonymous, and cross-jurisdictional characteristics of crypto assets make them an effective means of concealing the illicit origin of criminal proceeds. Within the national legal framework, the regulation of money laundering under Law Number 8 of 2010 has not explicitly accommodated crypto asset transactions, resulting in normative gaps and legal uncertainty. These issues are reflected in the Supreme Court of the Republic of Indonesia Cassation Decision Number 2029 K/Pid.Sus/2023 concerning Indra Kesuma, also known as Indra Kenz. This study aims to analyze the legal reasoning underlying judicial decisions in money laundering cases involving crypto asset-based schemes and to formulate regulatory reform of money laundering laws based on a cyber criminology approach. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that judges adopted a progressive interpretation of Article 1 paragraph (1), Article 3, and Article 4 of the Anti-Money Laundering Law by qualifying crypto assets as proceeds of crime. The cyber criminology approach underscores the necessity of digital evidentiary systems and a comprehensive understanding of blockchain technology. Furthermore, existing regulations remain inadequate, necessitating normative reform that includes the definition of crypto assets, obligations for reporting suspicious transactions, and the integration of on-chain Know Your Customer (KYC) mechanisms to ensure legal certainty and effective law enforcement.